2019
DOI: 10.1016/j.dadm.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive stress test for prodromal Alzheimer's disease: Multiethnic generalizability

Abstract: Introduction Culturally fair cognitive assessments sensitive to detecting changes associated with prodromal Alzheimer's disease are needed. Methods Performance of Hispanic and non-Hispanic older adults on the Loewenstein-Acevedo Scale of Semantic Interference and Learning (LASSI-L) was examined in persons with amnestic mild cognitive impairment (aMCI) or normal cognition. The association between a novel cognitive marker, the failure to recover from proactive semantic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
(56 reference statements)
2
14
0
Order By: Relevance
“…This is not surprising in that our previous work shows that both types of PreMCI have similar patterns and rates of progression to a formal diagnosis of MCI [19]. In additional post hoc analyses, we found no evidence in this study that Hispanic ethnicity, age, or sex influenced the obtained results, consistent with our recent findings [29] and demonstrating that the LASSI-L is equally effective diagnostically among Hispanics and non-Hispanics.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is not surprising in that our previous work shows that both types of PreMCI have similar patterns and rates of progression to a formal diagnosis of MCI [19]. In additional post hoc analyses, we found no evidence in this study that Hispanic ethnicity, age, or sex influenced the obtained results, consistent with our recent findings [29] and demonstrating that the LASSI-L is equally effective diagnostically among Hispanics and non-Hispanics.…”
Section: Discussionsupporting
confidence: 89%
“…Participants are tested in their preferred language (English vs. Spanish). The LASSI-L has been shown to be culturally fair in either language [29].…”
Section: Methodsmentioning
confidence: 99%
“…This cognitive stress test represents a novel paradigm that employs controlled learning and cued recall to maximize storage of a list of to‐be‐remembered target words representing three semantic categories 17 . Participants were tested in their preferred language (English vs Spanish) and the LASSI‐L has been shown previously to be culturally fair and valid in either language 30,50 …”
Section: Methodsmentioning
confidence: 99%
“…26,31 The failure to recover from PSI in particular has been strongly associated with volumetric reductions in areas prone to AD neurodegeneration (hippocampus, precuneus, inferior temporal lobules, superior parietal areas, and temporal pole), among persons with amnestic MCI (aMCI), whereas traditional neuropsychological tests have shown no or only weak associations. [35][36][37] Recently, it was found that intrusion errors produced on the LASSI-L scales tapping into PSI and frPSI were able to successfully differentiate individuals with aMCI who were amyloid positive (presumably prodromal AD) from other aMCI groups who were amyloid negative 35 ; however, the limitation of this previous work was that amyloid-negative MCI individuals were not classified according to the underlying etiology (neurological vs non-neurological impairment) and no cognitively normal group was included for comparison purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, culture/language significantly predicted digit span scores even after controlling for age, education, fluid memory score, and language syllable-length differences indicating that chunking is less impacted by cultural bias [ 116 ]. Furthermore, some commonly used AD assessments are even less susceptible to cultural bias, like the Loewenstein-Acevedo Scales for Semantic Interference and Learning (LASSI-L) [ 117 ]. While culture/language differences do not always impact the metrics used to assess functional decline associated with AD, but that is not to say that differences due to language are negligible.…”
Section: Alzheimer’s Disease and Cultural Group Disparitiesmentioning
confidence: 99%